Optimalisasi Perkembangan Fisik dan Motorik serta Pengembangan Manajemen - Robbie, R. Iqbal; Novianti, Khusnul Rofida; Ahadiyanto, Nuzul (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose – This community service aims to optimize physical and motor development in early childhood using the Participatory Action Research (PAR) method at KB-TKIT Rumah Pelangi, Batu City, Malang Design/methodology/approach – This method focuses on active participation for young children by using various game schemes to optimize physical and motor development, both fine and gross. Apart from this, there are aspects of management development in the aspects of planning, organizing, implementing, and supervising the management of KB-TKIT Rumah Pelangi Findings – The results of this activity are improvements in fine and gross motor skills for children as well as improvements in management aspects of KB-TKIT Rumah Pelangi, Batu City, Malang Originality/value – Shaping the character of students from an early age so that they grow into superior quality students